A presença da cultura popular em três grandes eventos na cidade de João Pessoa: Fernart, são joão e festa das neves em 2010 - Pinheiro, Camila Maria Gomes (2011)
This study addresses the participation of popular culture at festivals and events in the city of Joao Pessoa in 2010, as FENART, the party of the Snows and St. John From the field research was possible to see how these groups fit cultural programming in the city. The different treatment to see possible ambiguities in the enhancement of culture. The three events were to include different forms of popular culture. In FENART there was an unequal treatment and disrespectful to the popular groups, in view of the size of the event. Longed to meet a certain type of audience. The St. John separated the stage, and put the different times, and has given greater visibility to the gangs. On the Feast of the Snow was a change that improved the participation of popular culture, the festival focused on a single space and switching times. The survey is conducted from the speech of teachers.